2023
DOI: 10.1039/d2sc07014f
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided semi-rational design of an imine reductase for enantio-complementary synthesis of pyrrolidinamine

Abstract: In this study, engineered imine reductases (IREDs) of IRED M5, originally from Actinoalloteichus hymeniacidonis, were obtained through structure-guided semi-rational design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(88 reference statements)
0
4
1
Order By: Relevance
“…PmIR-Re represents an engineered IRED with completely reversed stereoselectivity (>99% ee) achieved through mechanism-guided computational design. In contrast to the previously reported residues W210 in AspRedAm 31 and W234/F260 in IRED-M5, 32 which potentially affect stereoselectivity by steric hindrance of the bulky side chain, the stereoselectivity in PmIR could be controlled by electrostatic interactions between the iminium cation and the acidic amino acids adjacent to the nicotinamide moiety of NADPH. Therefore, the stereoselectivity of IREDs can be tailored through rational reconstruction of electrostatic interactions and reshaping of the binding pocket.…”
Section: Complete Reversion Of Stereoselectivity Using Computational ...contrasting
confidence: 84%
“…PmIR-Re represents an engineered IRED with completely reversed stereoselectivity (>99% ee) achieved through mechanism-guided computational design. In contrast to the previously reported residues W210 in AspRedAm 31 and W234/F260 in IRED-M5, 32 which potentially affect stereoselectivity by steric hindrance of the bulky side chain, the stereoselectivity in PmIR could be controlled by electrostatic interactions between the iminium cation and the acidic amino acids adjacent to the nicotinamide moiety of NADPH. Therefore, the stereoselectivity of IREDs can be tailored through rational reconstruction of electrostatic interactions and reshaping of the binding pocket.…”
Section: Complete Reversion Of Stereoselectivity Using Computational ...contrasting
confidence: 84%
“…However, previous studies have indicated that the L200 amino acid site is highly conserved, leading to inactivation in most mutations. 24 The S -selectivity at the F260 site also increased with the introduction of larger side chain amino acid residues. An increase in the ee value was observed when M203 was mutated to leucine, and W234 to alanine and phenylalanine.…”
Section: Introductionmentioning
confidence: 99%
“…23 In the following year, we developed a semi-rational design approach to identify key residues 260, 200, 149, and 234 that play a crucial role in achieving excellent enantioselectivity. 24,25 In light of these results, we envisaged the opportunity to further explore the potential of this mutant through semi-rational design for the synthesis of ( S )-2-aminotetralin 1a of the rotigotine molecule (Fig. 2B).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we successfully developed the IR36-M5 mutant capable of catalyzing reactions involving piperidines and azepane alkylamines while also enhancing and reversing stereocenters [ 37 , 38 ]. Specifically, when utilizing propargylamine a as the donor, both pyrrolidinone and oxo-azepane exhibited outstanding R -stereoselectivity, achieving 98% and 99% ee values, respectively.…”
Section: Introductionmentioning
confidence: 99%